Pengaruh Kompetensi Perangkat Desa, Partisipasi Masyarakat, Komitmen Organisasi Dan Transparansi Terhadap Akuntabilitas Pengelolaan Dana Desa - Riyadi, Padlah (Institute Of Advanced Knowledge and Science, 2024)
The aim of the research is to test and provide empirical evidence of the influence of village officials' competence, community participation, organizational commitment and transparency on the accountability of village fund management. This research was conducted using a sample determination method, namely purposive sampling, with a quantitative research type. Data analysis was carried out using a multiple regression analysis model. Hypothesis testing was carried out to determine the extent of influence of village apparatus competence, community participation, organizational commitment and transparency on accountability in managing village funds, either partially or simultaneously. The results of hypothesis testing show that the competence of village officials has no effect on the accountability of village fund management, while community participation, organizational commitment and transparency have a positive effect on the accountability of village fund management.